2015
DOI: 10.1016/j.micromeso.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical MOF-xerogel monolith composites from embedding MIL-100(Fe,Cr) and MIL-101(Cr) in resorcinol-formaldehyde xerogels for water adsorption applications

Abstract: Shaping of otherwise powdery metal-organic frameworks is recognized as a more-and-more important issue to advance them to the application stage. Monolithic MOF composites were synthesized using micro-to-mesoporous MIL-100(Fe,Cr) and MIL-101(Cr) as thermally and chemically stable MOFs together with a mesoporous resorcinol-formaldehyde based xerogel as binding agent. The monolithic bodies could be loaded with up to 77 wt% of powdery MIL material under retention of the MIL surface area and porosities (from N 2 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 87 publications
4
55
0
Order By: Relevance
“…mean pore size 10 nm according to mercury porosimetry) in the OX-10 sample causes its water capacity to increase dramatically in the 0.9 < p/ p 0 < 1 interval, whilst sample OX-2100 displays the lowest total water adsorption capacity of the series studied due to the fact that its pores are too wide to play an important role in the adsorption of water. The water vapour adsorption isotherm obtained for this sample (OX-2100) is corroborated by others in the literature [43] corresponding to RF-xerogels with similar porosity that is not adequate for water adsorption applications. Therefore, although all RF-xerogels present hydrophilic character, not all of them can be used as desiccants but only the ones with the proper porosity.…”
Section: Desiccant Behavioursupporting
confidence: 82%
“…mean pore size 10 nm according to mercury porosimetry) in the OX-10 sample causes its water capacity to increase dramatically in the 0.9 < p/ p 0 < 1 interval, whilst sample OX-2100 displays the lowest total water adsorption capacity of the series studied due to the fact that its pores are too wide to play an important role in the adsorption of water. The water vapour adsorption isotherm obtained for this sample (OX-2100) is corroborated by others in the literature [43] corresponding to RF-xerogels with similar porosity that is not adequate for water adsorption applications. Therefore, although all RF-xerogels present hydrophilic character, not all of them can be used as desiccants but only the ones with the proper porosity.…”
Section: Desiccant Behavioursupporting
confidence: 82%
“…Under vigorous stirring, HKUST‐1 irreversibly adsorbs at the interface of the CO 2 –water system, forming a thermodynamic stable C/W emulsion . Some studies revealed that MOF/HIPE polymer composites can be synthesized by other methods . The remarkable superiority of our work is its environmentally friendly procedure and simple post‐treatment.…”
Section: Introductionmentioning
confidence: 93%
“…The band located at 1474 cm -1 corresponds to CH 2 deformation vibrations and the one at 1613 cm -1 to the aromatic ring stretching vibration (C=C). Stretching vibration bands at 1217 and 1092 cm -1 indicate the presence of methylene ether bridges C-O-C), although they should be not dominant as they were not detected by NMR [23,24]. It should also be noted that, as in the case of NMR, FTIR revealed identical bands in both organic samples, indicating similar chemical compositions.…”
Section: Resultsmentioning
confidence: 99%